(untitled) (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY In daily clinical work, coercion continues to be highly prevalent, with rates differing between countries and sometimes even within countries or between wards of the same hospital. Previous research found inconsistent characteristics of individuals who underwent coercive measures during psychiatric treatment. Furthermore, there continues to be a lack of knowledge on the clinical course of people after being involuntarily committed. This study aimed to describe the rate and duration of different coercive measures and characterise a cohort of involuntarily committed patients regarding sociodemographic and clinical variables. METHODS In this observational cohort study, we analysed clinical data from the patients’ medical files, the use of coercive measures (seclusion, restraint, coercive medication) and other procedural aspects in involuntarily hospitalised patients (n = 612) at the University Hospital of Psychiatry Zurich. For analysis, we used cross-tabulation with chi-square tests for categorical variables and, owing to a non-normal distribution, the Mann-Whitney U-test for interval variables. RESULTS Coercive measures were documented in 170 patients (28% of those who were involuntarily hospitalised). The total number of seclusions was 344, with a mean duration of 9 hours per seclusion. A total of 89 patients (15%) received 159 episodes of coercive medication (oral and intramuscular). Also, 11 episodes of restraint were recorded in 7 patients (1%) with a mean duration of 12 hours per restraint. Patients subjected to coercion were significantly more often male, violent prior to admission, diagnosed with psychosis or personality disorder, and had a history of frequent hospitalisations with long durations of hospitalisation. CONCLUSIONS The prevalence of coercive measures is still high in involuntarily hospitalised patients. Seclusion was the most frequently used coercive measure, which may be based on cultural and clinical aspects and differs from findings in other countries where restraint is more frequently used. Some sociodemographic and clinical characteristics were associated with the use of coercion. This underlines the importance of developing treatment strategies for patients at risk to prevent situations in which the use of coercion is necessary. To enable comparison between different study sites, standardised protocols should be used to document frequency and duration of coercive measures.